2018
DOI: 10.5201/ipol.2018.229
|View full text |Cite
|
Sign up to set email alerts
|

An Analysis and Implementation of the Harris Corner Detector

Abstract: In this work, we present an implementation and thorough study of the Harris corner detector. This feature detector relies on the analysis of the eigenvalues of the autocorrelation matrix. The algorithm comprises seven steps, including several measures for the classification of corners, a generic non-maximum suppression method for selecting interest points, and the possibility to obtain the corners position with subpixel accuracy. We study each step in detail and propose several alternatives for improving the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(24 citation statements)
references
References 19 publications
0
22
0
2
Order By: Relevance
“…In order to perform the translation operation, the interest points, such as corners, are determined using the Harris corner detector operator ( R ) [ 25 , 26 ]. Corners are the key features of the morphology of brain images.…”
Section: Methodsmentioning
confidence: 99%
“…In order to perform the translation operation, the interest points, such as corners, are determined using the Harris corner detector operator ( R ) [ 25 , 26 ]. Corners are the key features of the morphology of brain images.…”
Section: Methodsmentioning
confidence: 99%
“…Didapatkan hasil akurasi diatas 97% dan tingkat presisi objek sebesar 100%. Pengunaan metode Harris Corner akan menghasilkan nilai yang konsiten dari suatu citra walaupun telah mengalami rotasi, penskalaan, variasi pencahayaan, ataupun memiliki noise seperti pada penelitian sebelumnya [4]. Kesimpulannya bahwa metode Hough Transform dan Harris Corner tersebut layak untuk digunakan dalam proses cropping bagian plat nomor kendaraan.…”
Section: Pendahuluanunclassified
“…Metode ini digunakan untuk mendeteksi sudut pada citra, dimana pada sistem ini metode Harris Corner bertujuan untuk mendeteksi sudut pada plat nomor kendaraan yang akan menandakan bahwa plat tersebut berbentuk persegi panjang yang sempurna dengan adanya sudut-sudut tersebut. Metode ini akan menghasilkan nilai yang konsiten dari suatu citra walaupun telah mengalami rotasi, penskalaan, variasi pencahayaan, ataupun memiliki noise [4]. Untuk melakukan proses ini dilakukan langkah-langkah sebagai berikut: 1) Konversi citra biner ke grayscale Hasil keluaran Hough Transform berupa citra biner, maka dari itu harus diubah ke dalam citra grayscale dengan persamaan berikut = 255 * .…”
Section: E Harris Cornerunclassified
“…We aimed to resolve the problems of result variations caused by user bias, automation difficulties, and the increased uncertainty incurred when hyperspectral imaging is used to apply the image registration technique. To maintain result consistency and reduce uncertainty, we applied image displacement tracking technology, based on the optical flow algorithm, and Harris corner detection technology [ 26 , 27 ] for extracting corners. It has been reported that optical flow can reduce the uncertainty caused by user inputs and is less affected by rotation and scale than template matching.…”
Section: Introductionmentioning
confidence: 99%